Novel Hybrid Recursive Active Filters in RF Transmitter Front-Ends - Gottardo, Giuseppe; Donati, Giovanni; Musolff, Christian; Weigel, Robert; Fischer, Georg (German Microwave Conference, 2014)
Duplex filters in modern base stations are designed as cavity filters, which are expensive and have big dimensions. In order to reduce the size of these filters a novel hybrid system using a power amplifier and a negative digital feedback for frequency band GSM900 is studied. A model to describe the hybrid system is investigated and the relation between phase and resonance peaks in the transfer function is described. An attenuation of 5.4 dB for the closed loop transfer function is reached. The stability condition of the system is here presented using Nyquist criterion as an important step for its future feasibility.
elib2cris::1512001600,gottardo2014
Keywords: Active filter; feedback amplifier; base station; stability analysis; interference suppression; band-pass filters; cavity resonators